Optimization of total RNA extraction from sperm and detection of phospholipase C zeta gene fragments from sperm, testis and epididymis of Oryctolagus cuniculus - Samsul Baharil, Nur Hayati (2013)
Fertilization is defined as the fusion of sperm to an ovum to form a fertilized egg. As capacitated sperm fuse with the ovum, the acrosome reaction occurs to digest the corona radiata and zona pellucida that surrounds the ovum. A single sperm will then bind to the oocyte's membrane receptor, while its nucleus is engulfed by the ooplasm. A sperm specific factor, the Phospholipase C ζ (PLC ζ) is then released from the sperm which led to activation of the ovum, embryo development as well as block to polyspermy. Recent studies have demonstrated that sperm RNA is known to play essential roles during fertilization since it sustains long-lasting calcium response. Nevertheless, there is no established method to extract RNA from sperm pertaining to little amount in spermatic RNA. Therefore, the isolation of RNA from sperm Oryctolagus cuniculus (O. cuniculus) was studied. Optimization on four different methods with different chemical reagents were conducted; the method of collecting fresh semen alone, centrifuged at 4000 rpm for 10 minutes prior to RNA extraction using Easy Blue Total RNA Extraction kit was done as control group. For methodology 1, the pooled ejaculate was centrifuged with the same speed and duration before proceeding with total RNA extraction using Easy Blue Total RNA Extraction kit. Fresh semen was collected for methodology 2 and was centrifuged prior to total RNA extraction using Easy Red Total RNA Extraction kit. Next, methodology 3 was done by collecting fresh semen that was washed in phosphate buffered saline (PBS) during centrifugation before the usage of Easy Blue Total RNA Extraction kit. Finally, fresh semen washed in PBS was further purified using EquiPure and total RNA was extracted using Easy Blue Total RNA Extraction kit was performed as methodology 4. Besides sperm, total RNA from testis and epididymis were also extracted using Easy-Blue Total RNA Extraction kit. The RNA obtained from sperm, testis and epididymis were quantified in spectrophotometer to verify the concentration and purity of total RNA obtained. The target gene was then amplified using One-Step Reverse Transcriptase (RT)-PCR. The band that appeared on gel electrophoresis was excised and purified using Fermentas Gel Extraction kit before sending to sequencing company. Hence, by performing methodology 3, the total RNA from sperm of Oryctolagus cuniculus with the best total RNA purity and concentration ranging from 1.6 to 1.8 at absorbance of A260/280 and 440 to 570 ng/μl respectively was successfully isolated. Beside sperm, testis and epididymis that carried specific code for sperm factor known as PLC ζ was successfully isolated and amplified. Thus, all three samples size is from 400 to 500 base pairs. Target protein from testis and epididymis indicated 87% and 85% highly similar to Nomascus leucogenys PLC ζ sequence in NCBI database respectively. The sequence obtained from this study could be the reference for future studies.